Downregulation of Mitofusin 2 in Placenta Is Related to Preeclampsia. (31st January 2016) - Yu, Jun; Guo, Xijiao; Chen, Ruibao; Feng, Ling
Abstract : Background . Mitofusin 2 (Mfn2) is a novel mitochondrial protein that is implicated in cellular proliferation and metabolism; however, the role of Mfn2 in preeclampsia (PE) remains unknown. This study aimed to explore the relationship between Mfn2 and PE. Method . Preeclamptic and normal pregnancies were enrolled in a comparative study. The expression of Mfn2 in placenta was detected by qRT-PCR. And the mitochondrial function was detected by ATP assay. Then TEV-1 cells were cultured in hypoxic conditions. mRNA and protein expressions of Mfn2 were detected by qRT-PCR and western blot separately. Cells' viability was detected by MTT. And the mitochondrial function was detected by ATP and mitochondrial membrane potential (MMP) assay. We further knocked down the Mfn2 gene in TEV-1 cells and evaluated the cells' viability. Results . Mfn2 and ATP expressions were significantly decreased in preeclamptic placentae compared to normal placentae. Mfn2 expression level and the viability of TEV-1 cells were reduced during hypoxic conditions. TEV-1 cells' viability, ATP, and MMP levels were also significantly decreased after knockdown of the Mfn2 gene. Conclusions . These results suggest that defects in Mfn2 could cause mitochondrial dysfunction and decrease trophoblastic cells' viability. Therefore, Mfn2 may be functionally involved in the pathogenesis of PE.